The Impact of Leadership Style, Employee Motivation, and Organizational Culture on Job Performance of Start-Up Employee - Sihite, Mislan; Soegiarto, Ita; Ilmi, Makrifatul; Ilham, Ilham (IJBLE Scientific Publications Community Inc., 2024)
This research explores the impact of leadership style, employee motivation, and organizational culture on job performance in start-up companies. The study adopts a quantitative research design, collecting data from employees in various start-ups through a cross-sectional survey method. Descriptive statistics, reliability analysis, correlation analysis, multiple regression analysis, and moderation analysis are employed to analyze the data. The results indicate that transformational leadership, intrinsic motivation, and a positive organizational culture significantly enhance job performance. Transactional leadership and extrinsic motivation also contribute positively but to a lesser extent. Organizational culture and employee motivation are identified as crucial moderators, amplifying the effects of leadership styles on job performance. These findings underscore the importance of effective leadership, motivational factors, and a supportive organizational culture in driving job performance within start-up environments.